TRANSFORMASI MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN: TINJAUAN TEORITIS DAN PENDEKATAN STRATEGIS DI ERA DIGITAL - Rawis, Joulanda A. M.; Sumual, Shelty D. M.; Akay, Freili; Berhandus, Catrien; Razak, Farid Abdul (STKIP Pesisir Selatan, 2025)
Objective: This study aims to analyze the transformation of educational infrastructure management in the digital era and formulate a strategic framework integrating Total Quality Management (TQM) and Smart Asset Management to improve service effectiveness. Methods: The research utilizes a qualitative library research method. Data were collected from 40 selected academic documents, including reputable scientific journals and government regulations, published between 2020 and 2025. The data analysis employs a thematic content analysis technique to identify trends, managerial barriers, and strategic solutions relevant to the Indonesian context. Results: The study reveals that infrastructure inefficiency stems from a failure in managerial paradigms, particularly the lack of maintenance culture, rather than merely budget deficits. The integration of TQM through preventive maintenance cycles and the adoption of IoT-based inventory systems (Smart Asset Management) and virtual laboratories are identified as key strategies to extend asset lifespan and optimize operational costs. Novelty: This article offers novelty by proposing a